2006
DOI: 10.1002/ps.1311
|View full text |Cite
|
Sign up to set email alerts
|

Demonstrating formation of potentially persistent transformation products from the herbicides bromoxynil and ioxynil using liquid chromatography‐tandem mass spectrometry (LC‐MS/MS)

Abstract: It is shown that potentially persistent transformation products can be formed from the herbicides bromoxynil (3,5-dibromo-4-hydroxybenzonitrile) and ioxynil (3,5-diiodo-4-hydroxybenzonitrile), and possible leaching to groundwater is discussed. A similar process to the formation of BAM (2,6-dichlorobenzamide) from the herbicide dichlobenil (2,6-dichlorobenzonitrile) can be anticipated as bromoxynil and ioxynil are analogues of dichlobenil and they are degraded by the enzymes nitrilase, nitrile hydratase and ami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 46 publications
3
15
1
Order By: Relevance
“…One can conclude that the ability to provide protons increases in order p-hydroxybenzonitrile (pK a = 8.0) < ioxynil 3 (pK a = 4.0) < 3-chloro-4-hydroxybenzonitrile 2 (pK a not available) < chloroxynil 1 (pK a = 3.1). This is in agreement with the decreasing pK a of these compounds reported in literature [24,25].…”
Section: Resultssupporting
confidence: 92%
“…One can conclude that the ability to provide protons increases in order p-hydroxybenzonitrile (pK a = 8.0) < ioxynil 3 (pK a = 4.0) < 3-chloro-4-hydroxybenzonitrile 2 (pK a not available) < chloroxynil 1 (pK a = 3.1). This is in agreement with the decreasing pK a of these compounds reported in literature [24,25].…”
Section: Resultssupporting
confidence: 92%
“…The supposed soil issue of persistent benzonitrile–herbicide metabolites, as raised in the literature, is somewhat contradicted by the capabilities of the indigenous soil microbiota in the current study, as ioxynil and bromoxynil were mineralized quickly, irrespective of previous benzonitrile exposure. Rosenbrock et al also reported bromoxynil degradation in soil with 20–30% CO 2 recovery within 5 days.…”
Section: Discussioncontrasting
confidence: 81%
“…), it has been proposed that ioxynil and bromoxynil may be converted into persistent metabolites in the same way as dichlobenil is converted to BAM . In this context, Nielsen et al observed incomplete hydrolysis of ioxynil and bromoxynil by Variovorax sp. DSM 11402 to 3,5‐diiodo‐4‐hydroxybenzamide (IAM) and 3,5‐dibromo‐4‐hydroxybenzamide (BrAM), respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Rhizobium radiobacter (formerly Agrobacterium radiobacter; Vosáhlová et al 1997;Holtze et al 2006) and Variovorax sp. (Nielsen et al 2007) not only converted dichlobenil, but also bromoxynil and ioxynil into the corresponding amides. Alternatively, bromoxynil and ioxynil were hydrolyzed into carboxylic acids by the nitrilase of Klebsiella pneumoniae ssp.…”
Section: Introductionmentioning
confidence: 98%